In Situ Evaluation of Oxidative Stress in Rat Fatty Liver Induced by a Methionine- and Choline-Deficient Diet. (6th January 2016) - Freitas, Isabel; Boncompagni, Eleonora; Tarantola, Eleonora; Gruppi, Cristian; Bertone, Vittorio; Ferrigno, Andrea; Milanesi, Gloria; Vaccarone, Rita; Tira, M. Enrica; Vairetti, Mariapia
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a serious health problem in developed countries. We documented the effects of feeding with a NAFLD-inducing, methionine- and choline-deficient (MCD) diet, for 1–4 weeks on rat liver oxidative stress, with respect to a control diet. Glycogen, neutral lipids, ROS, peroxidated proteins, and SOD2 were investigated using histochemical procedures; ATP, GSH, and TBARS concentrations were investigated by biochemical dosages, and SOD2 expression was investigated by Western Blotting. In the 4-week-diet period, glycogen stores decreased whereas lipid droplets, ROS, and peroxidated proteins expression (especially around lipid droplets of hepatocytes) increased. SOD2 immunostaining decreased in poorly steatotic hepatocytes but increased in the thin cytoplasm of macrosteatotic cells; a trend towards a quantitative decrease of SOD expression in homogenates occurred after 3 weeks. ATP and GSH values were significantly lower for rats fed with the MCD diet with respect to the controls. An increase of TBARS in the last period of the diet is in keeping with the high ROS production and low antioxidant defense; these TBARS may promote protein peroxidation around lipid droplets. Since these proteins play key roles in lipid mobilization, storage, and metabolism, this last information appears significant, as it points towards a previously misconsidered target of NAFLD-associated oxidative stress that might be responsible for lipid dysfunction.